The Link Between Responsibility and Legitimacy: The Case of De Beers in Namibia - Claasen, Cyrlene; Roloff, Julia (2012)
This article investigates the link between corporate social responsibility (CSR) practices and the reasons for which legitimacy is ascribed or denied. It fills a gap in the literature on CSR and legitimacy that lacks empirical studies regarding the question whether CSR contributes to organisational legitimacy. The problem is discussed by referring to the case of De Beers’s diamond mining partnership with the Government of Namibia. A total of 42 interviews were conducted—41 with stakeholders and one with the focal organisation Namdeb. The 41 stakeholder interviews are analysed with regard to cognitive, pragmatic and moral legitimacy as defined by Suchman (Acad Manage Rev 20(3):571–610, 1995). The main finding is that the majority of statements on organisational legitimacy refer to moral legitimacy and most issues raised in this context challenge the company’s legitimacy despite its comprehensive CSR engagement. The study demonstrates that legitimacy gaps can be a result of communication practices that raise unrealistic stakeholder expectations and that the legitimacy gained by CSR engagement in one area cannot substitute legitimacy losses caused by failures in another.
Keywords: Public private joint venture; Namibia; Namdeb; De Beers; Corporate Social Responsibility; Social Responsibility; Legitimacy